Exploring the enablers and barriers experienced by people with severe and enduring mental illnesses in Jamaica when accessing healthcare for chronic physical illnesses - Whitehorne-Smith, Patrice Antoinette (Curtin University, 2023)
This study utilised a convergent mixed-methods design to explore the enablers and barriers to healthcare access for people with severe and enduring mental illness and chronic physical illness in Jamaica. Findings revealed enablers and barriers operated across a socio-ecological model consisting of factors consistent with several social determinants of health including free healthcare, poverty, stigma and discrimination and social support. Implications and recommendations for improved healthcare access for this population were presented and discussed.